COMBUSTION OF LOW-RANK COALS IN TURNASES OF KAZAKHSTAN COAL-FIRING POWER PLANS - Askarova, A.S.; Bolegenova, S.A.; Maksimov, V.Ju. (Recent Contributions to Physics, 2018)
The simulation of the combustion in the concurrent flow of    low-rank coals in turnases of Kazakhstan coal-firing power plans has been performed. Numerical solution of the systems of differential three-dimensional stationary equations of turbulent reacting boundary layer has been obtained. The study of the influence of the initial factors on the process of combustion and formation of NOx has been carried out.